Sports Nutritional Assessment and Its Application for Elite Athletes: 優秀運動員運動營養調査與跟踪 - GAO, Xia; CHIN, Ming Kai (Asian Journal of Physical Education & Recreation, 1995)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Sports nutrition is an important part in modem sports science area. Since sports nutrition is very different from general nutrition, its quality and diet system should be designed to the change of physiological and chemical responses in different exercise situation. The purpose of the optimal nutrition for athletes is to meet the physiological need, avoid the over-training fatigue, and provide the advantage edge for training and competition. A complete nutritional survey includes diet report, clincial check-up of nutrient-deficiency disease, and biochemical examination. The biochemical examination is very important for objective assessment and food supplements for individual athletes. Sports nutritionists should possess the knowledge of sports physiology, and sports biochemistry, and have the on-field experiences with the training sessions in order to meet the needs of the coach and athlete.